Metal-Induced Stabilization and Activation of Plasmid Replication Initiator RepB - Ruiz-Masó, José A.; Bordanaba-Ruiseco, Lorena; Sanz, Marta; Menéndez, Margarita; del Solar, Gloria (Frontiers in Molecular Biosciences, 2016)
Initiation of plasmid rolling circle replication (RCR) is catalyzed by a plasmid-encoded Rep protein that performs a Tyr- and metal-dependent site-specific cleavage of one DNA strand within the double-strand origin (dso) of replication. The crystal structure of RepB, the initiator protein of the streptococcal plasmid pMV158, constitutes the first example of a Rep protein structure from RCR plasmids. It forms a toroidal homohexameric ring where each RepB protomer consists of two domains: the C-terminal domain involved in oligomerization and the N-terminal domain containing the DNA-binding and endonuclease activities. Binding of Mn2+ to the active site is essential for the catalytic activity of RepB. In this work, we have studied the effects of metal binding on the structure and thermostability of full-length hexameric RepB and each of its separate domains by using different biophysical approaches. The analysis of the temperature-induced changes in RepB shows that the first thermal transition, which occurs at a range of temperatures physiologically relevant for the pMV158 pneumococcal host, represents an irreversible conformational change that affects the secondary and tertiary structure of the protein, which becomes prone to self-associate. This transition, which is also shown to result in loss of DNA binding capacity and catalytic activity of RepB, is confined to its N-terminal domain. Mn2+ protects the protein from undergoing this detrimental conformational change and the observed protection correlates well with the high-affinity binding of the cation to the active site, as substituting one of the metal-ligands at this site impairs both the protein affinity for Mn2+and the Mn2+-driven thermostabilization effect. The level of catalytic activity of the protein, especially in the case of full-length RepB, cannot be explained based only on the high-affinity binding of Mn2+ at the active site and suggests the existence of additional, lower-affinity metal binding site(s), missing in the separate catalytic domain, that must also be saturated for maximal activity. The molecular bases of the thermostabilizing effect of Mn2+ on the N-terminal domain of the protein as well as the potential location of additional metal binding sites in the entire RepB are discussed.